Natural resources, financial development and economic growth in selected MENA countries - Daouia, Chebab (2020)
Natural resources have been identified to be a significant source of revenue and wealth for resource-abundant developing countries. In this regard, the Middle East and North Africa (MENA) region has one of the world’s largest natural resource endowments. Although representing only 7.5 percent of the world’s population, the MENA region holds 48 and 52 percent of the world’s oil and gas reserves respectively. Despite the strategic importance of natural resources in the resource-rich countries, defined as the leading producers and exporters of oil and gas, there is limited empirical evidence on their economic impact and how they affect the financial development in the region. Furthermore, theoretical considerations imply that the abundance of natural resources might have significant long-run impacts on economic growth and financial development. However, most existing studies disregard the role of financial development in estimating the long-run growth impact of natural resource abundance, and do not indicate the various channels through which natural resource abundance affects financial development in MENA. To this end, the current research is set for examining these issues through three objectives for a core sample of 11 selected MENA countries over the period 1987-2015. The first objective investigated the long-run impact of resource abundance on economic growth while accounting for the interaction effect of financial development in resource-abundant MENA countries. In doing so, the Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares were employed. Results indicated positive and significant evidence of the long-run impact of natural resources on economic growth. In the second objective, Pooled Mean Group (PMG), Mean Group (MG), and Dynamic Fixed Effect (DFE) were employed to determine the channels explaining the relationship between natural resource abundance and the financial development. Findings revealed that only the corruption channel explained the significant negative impact of natural resources on the level of financial development. Finally, the third objective considered the possible existence of threshold level(s) for financial development on economic growth by employing PMG, MG, and DFE models. Empirical results suggested the presence of non-linear and inverted U-shaped for the relationship between financial development and economic growth. Findings from this study have suggested that the abundance of natural resources can generate long-run economic growth in resource-abundant MENA countries. However, the impact of growth will be even more pronounced in countries with a relatively lower financial development level. Additionally, the abundance of natural resources may hinder financial development by increasing opportunities for rent-seeking and corruption. Thus, resource-plenty countries in the MENA region will boost the level of financial development through minimizing the degree of corruption in their financial sectors. Moreover, the non-monotonic relationship between finance and growth implied that further investment in financial sector development depletes the long-run economic growth. These outcomes provide significant guidance to the policymakers in resource-rich MENA region to encourage the potential of financial development in boosting economic growth, by channeling the resource-rents into productive activities.